2001
DOI: 10.1002/tox.10008
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 14C cylindrospermopsin in vivo in the mouse

Abstract: Radiolabelled 14C cylindrospermopsin (CYN) has been prepared and used to investigate the distribution and excretion of CYN in vivo in male Quackenbush mice. At a dose of 0.2 mg/kg (i.e., approx. median lethal dose) the following mean (SD) urinary and faecal recoveries (cumulative) were obtained, respectively: (0-6 hours, n = 4) 48.2 (29.3)%, 11.9 (21.4)%; (0-12 hours, n = 12) 66.0 (27.1)%, 5.7 (5.6)%; (0-24 hours, n = 12) 68.4 (26.7)%, 8.5 (8.1)%. Mean (SD) recoveries from livers at 6 hours were 20.6 (6.4)% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Moreover, studies of the body distribution of 14C-labeled CYN in mice have shown that the main excretory route is through the kidneys, with nearly 50% of an intraperitoneally (i.p.) administered dose appearing in the urine within 6 h, and 20% of the dose present in the liver [37]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, studies of the body distribution of 14C-labeled CYN in mice have shown that the main excretory route is through the kidneys, with nearly 50% of an intraperitoneally (i.p.) administered dose appearing in the urine within 6 h, and 20% of the dose present in the liver [37]. …”
Section: Resultsmentioning
confidence: 99%
“…Norris et al [97] showed CYN accumulated into the liver and kidney of mice within six hours of dosing via IP injection. The accumulation rate progressively decreased over five to seven days, after a single dosing event.…”
Section: Bioaccumulation Of Cynmentioning
confidence: 99%
“…Radio-labelling of CYN would enable studies on whether the toxin can permeate all cell membranes [87]. However, only one report has been made of such a study using 14 C-labelling in mice [97]. …”
Section: Where To Next?mentioning
confidence: 99%
“…Moreover, studies of the body distribution of 14 C-labeled CYN in mice showed that CYN was mainly excreted through the kidney, as nearly 50% of an i.p. administered dose of CYN appeared in the urine in 6 h, whereas 20% of the dose was present in the liver [42]. …”
Section: Resultsmentioning
confidence: 99%